Trace metal speciation in a wastewater wetland and its bioaccumulation in tilapia Oreochromis niloticus. Issue 1 (1st January 2018) - Aldana, G.; Hernández, M.; Cram, S.; Arellano, O.; Morton, O.; Ponce de León, C.
Abstract: Trace metal species in the water column of a canal system forming a wetland filled with wastewater were analyzed to determine their correlation with metal accumulation in the gills of locally fished Oreochromis niloticus . The metal concentrations in the suspended particles and water dissolved were analyzed. The metal species were calculated using Windermere Humic Aqueous Model version VII showing that the high organic matter and major cation contents were important parameters. Also, the free ion metal concentration was expected to correlate with the organic matter aromaticity; however, organic compounds other than humic susbtances seem to be complexing the metals in the system. Additionally, no clear correlation could be found between metal accumulation in gills and any of the dissolved metal species. Nonetheless, certain trends could be seen between the calculated metal species and metal accumulation in the tilapia from the suspended particles.